Detection of nontoxic BoNT/A levels in post-facial Botox injection breastmilk - Gu, Helene; Xu, Zhenyu; Koviazina, Renata; Tan, Pengcheng; Zheng, Changcheng; Kappes, Ferdinand; Kotsifaki, Domna G.; Shen, Fangrong; Tsigkou, Anastasia (Frontiers in Drug Safety and Regulation, 2025)
The use of cosmetic Botox (BoNT/A) has become increasingly prevalent among women, even during the post-pregnancy breastfeeding period. However, there is currently a limited understanding of the extent Botox enters breastmilk and its potential effect on the breastfeeding infant. In this study, breastmilk samples were acquired from five women aged between 28 and 45. Three sample sets ranged from 1 h to 1 year after facial Botox treatments (64 U), whereas the remaining two were from women who never received Botox. BoNT/A concentrations in samples were detected using standard Enzyme-Linked Immunosorbent Assay (ELISA), unreduced and reduced Western Blotting, confocal micro-Raman Spectroscopy, and Mass Spectrometry (LC-MS). From ELISA, the greatest breastmilk BoNT/A concentration was found from woman 1, 4 days after Botox injection (167 pg/mL). Levels were highest overall in the first week (82.45–167 pg/mL) and around 2 months (132.725 pg/mL) after injection. No clear indication of BoNT/A was detected in Mass Spectrometry (LC-MS), Western Blotting and confocal micro-Raman Spectroscopy, but Western blot and confocal micro-Raman Spectroscopy show promise of development into future means of detection. From our study, the amount of BoNT/A in breastmilk peaks around 4 days (167 pg/mL) and at 2 months (132.725 pg/mL) after facial injection. Even over a year after injection, BoNT/A can be detected. However, all quantities of BoNT/A detected (between 34.4 pg/mL and 167 pg/mL) are likely to be safe for infants.